Cueing natural event boundaries improves memory in people with post-traumatic stress disorder - Barbara L. Pitts; Michelle L. Eisenberg; Heather R. Bailey; Jeffrey M. Zacks (Cognitive Research, 2023)
Abstract People with post-traumatic stress disorder (PTSD) often report difficulty remembering information in their everyday lives. Recent findings suggest that such difficulties may be due to PTSD-related deficits in parsing ongoing activity into discrete events, a process called event segmentation. Here, we investigated the causal relationship between event segmentation and memory by cueing event boundaries and evaluating its effect on subsequent memory in people with PTSD. People with PTSD (n = 38) and trauma-matched controls (n = 36) watched and remembered videos of everyday activities that were either unedited, contained visual and auditory cues at event boundaries, or contained visual and auditory cues at event middles. PTSD symptom severity varied substantial within both the group with a PTSD diagnosis and the control group. Memory performance did not differ significantly between groups, but people with high symptoms of PTSD remembered fewer details from the videos than those with lower symptoms of PTSD. Both those with PTSD and controls remembered more information from the videos in the event boundary cue condition than the middle cue or unedited conditions. This finding has important implications for translational work focusing on addressing everyday memory complaints in people with PTSD.